The effect of western conifer seed bug (Leptoglossus occidentalis Heidemann) on stone pine (Pinus pinea L.) seeds in Bursa - Bulut, Bülent; Kalkan, Mehmet; Yılmaz, Mustafa (Bursa Teknik Üniversitesi, 2022)
Stone pine (Pinus pinea L.) is one of the five natural pine species in Türkiye, and it is distributed in all Mediterranean coastal areas from Portugal to Anatolia. It naturally distiributes in the provinces of Artvin, Trabzon, Bartın, Bursa, İzmir, Aydın, Muğla, Antalya, Kahramanmaraş in Türkiye. In recent years, it has been reported that the western conifer seed bug (Leptoglossus occidentalis Heidemann) pierces the cones of coniferous tree species and damages their seeds. The insects insert their mouth stylets into the conifer tissue, it secretes digestive enzymes into the seed and sucks the embryos that it liquefies. Although the insect causes damage to many coniferous tree species, it has come to the forefront especially with the damage it causes to pine seed production in our country. In this study, the effect of western conifer seed bug (Leptoglossus occidentalis Heidemann) on stone pine (Pinus pinea L.) seeds in Bursa was investigated. Within the scope of the study, the average sound-empty-damaged seed ratios were determined as a result of the cutting test. According to the results of the cutting test, it was determined that the average insect damage was 61.2% in the three populations. The average sound seed rate in the three populations was 29.4%, and the average empty seeds rate was 9.4%. In order to determine the effect of insect damage on germination, the seed germination tests were conducted at 20 °C, after prechilling for 0 (control) and 4 weeks. The average germination rate was 13.8% in the control group, prechilling did not have a favorable effect on the germination percentage. The effect of the bug on the seeds of other coniferous species in our country should be investigated.

Fıstıkçamı (Pinus pinea L.) ülkemizde doğal yayılış gösteren beş çam türünden biri olup, Portekiz’den Anadolu’ya kadar tüm Akdeniz sahil kesimlerinde yayılış gösterir. Türkiye’de Artvin, Trabzon, Bartın, Bursa, İzmir, Aydın, Muğla, Antalya, Kahramanmaraş illerinde doğal olarak yayılış yapmaktadır. Son yıllarda çam kozalak emici böceği (Leptoglossus occidentalis Heidemann)’nin ibreli ağaç türlerinin kozalaklarını delerek tohumlarına zarar verdiği kaydedilmektedir. İğne şeklindeki ağız yapısıyla kozalak dokusuna iğnesini batırmakta, tohum içerisine sindirim enzimi salgılayarak sıvı hale getirdiği embriyoları sindirim sistemine çekerek beslenmektedir. Böcek çok sayıda ibreli ağaç türünde zarar yapmakla birlikte, ülkemizde özellikle çam fıstığı üretimine verdiği zararla ön plana çıkmış durumdadır. Bu çalışmada, çam kozalak emici böceği (Leptoglossus occidentalis Heidemann)‘nin Bursa’daki fıstıkçamı (Pinus pinea L.) tohumlarına etkisi araştırılmıştır. Çalışma kapsamında kesme testi sonucu ortalama dolu-boş-böcekli tohum oranları belirlenmiştir. Yapılan kesme testi sonuçlarına göre üç popülasyonda böcek zararı ortalaması %61.2 olduğu tespit edilmiştir. Üç popülasyonda doluluk oranları ortalaması %29.4, boş çıkan tohum oranları ortalaması ise %9.4 olarak belirlenmiştir. Böcek zararının çimlenmeye olan etkisini belirlemek amacıyla katlamasız (kontrol) ve 4 hafta soğuk katlamaya alınmış tohumlarda çimlenme testi gerçekleştirilmiştir. Kontrol grubunda ortalama %13,8 oranında çimlenme gerçekleşmiş, soğuk katlamanın çimlenme yüzdesine olumlu bir etkisi olmamıştır. Zararlının ülkemizde bulunan diğer ibreli türlerin tohumları üzerindeki etkisi araştırılmalıdır.
Çam Kozalak Emici Böceği (Leptoglossus occidentalis Heidemann)‘nin Bursa’daki Fıstıkçamı (Pinus pinea L.) Tohumlarına Etkisi
1919B012005602
Keywords: Forest Industry Engineering; Orman Endüstri Mühendisliği